2014
DOI: 10.3109/10253890.2014.967677
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss by calorie restriction versus bariatric surgery differentially regulates the hypothalamo-pituitary-adrenocortical axis in male rats

Abstract: Behavioral modifications for the treatment of obesity, including caloric restriction, have notoriously low long-term success rates relative to bariatric weight-loss surgery. The reasons for the difference in sustained weight loss are not clear. One possibility is that caloric restriction alone activates the stress-responsive hypothalamo-pituitary-adrenocortical (HPA) axis, undermining the long-term maintenance of weight loss, and that this is abrogated after bariatric surgery. Accordingly, we compared the HPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 49 publications
8
26
0
Order By: Relevance
“…The considerable reduction in overall SAT tissue that comprises twothirds of total adipose tissue, together with the near 50% reduction in SAT 11bHSD1 expression 1 year after surgery, could significantly account for the downshift of serum and tissue cortisol levels. Accordingly with our data, in rats, a reduction in HPA basal activity after bariatric surgery has been recently reported, in contrast to the HPA activation elicited by food-restriction to achieve body weight loss (22). In this context, correlations found between total cortisol and ACTH with body weight, BMI and adipose tissue are consistent with the increase in food intake and body weight elicited by glucocorticoids in humans (23).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The considerable reduction in overall SAT tissue that comprises twothirds of total adipose tissue, together with the near 50% reduction in SAT 11bHSD1 expression 1 year after surgery, could significantly account for the downshift of serum and tissue cortisol levels. Accordingly with our data, in rats, a reduction in HPA basal activity after bariatric surgery has been recently reported, in contrast to the HPA activation elicited by food-restriction to achieve body weight loss (22). In this context, correlations found between total cortisol and ACTH with body weight, BMI and adipose tissue are consistent with the increase in food intake and body weight elicited by glucocorticoids in humans (23).…”
Section: Discussionsupporting
confidence: 90%
“…The literature concerning this issue is scarce and, again, controversial. Data obtained for nonhealthy women with obesity 1 year or 2 years after bariatric surgery are consistent with our results, but those including men and women with healthy obesity are not .…”
Section: Discussionsupporting
confidence: 89%
“…The study of eight participants who were subjected to DER for 2 years in a closed ecological space (Biosphere 2) also showed increased morning total cortisol ( 157 ). Interestingly, Grayson et al ( 158 ) reported that rodent weight loss induced by DER increased basal HPA axis activity, unlike the same level of weight loss induced by bariatric surgery. Cortisol is usually released in a circadian rhythm, being an important aspect of the circadian system.…”
Section: Involvement Of Steroid Hormones In Dietary Interventionsmentioning
confidence: 99%
“…Although these findings are important and help to shed light on the mechanisms of metabolic surgery, there is ample evidence that food restriction plays a lesser role than initially expected (69,70). In line with these findings are recent studies showing that the fibroblast growth factor, a hormone that is relevant for energy consumption and mitochondrial function and the hypothalamic-adrenal axis is very differently affected by metabolic surgery than very-low-calorie diets (71,72). Further supporting the role of hormonal changes after metabolic surgery is the fact that the LAGB is clearly inferior to both SG and RYGB regarding long-term weight loss and T2DM remission (73,74).…”
Section: Mechanisms Of Metabolic Surgerymentioning
confidence: 62%